Genotype-Phenotype Correlation of SCN5A Genotype in Patients With Brugada Syndrome and Arrhythmic Events: Insights From the SABRUS in 392 Probands. (October 2021) - Milman, Anat; Behr, Elijah R.; Gray, Belinda; Johnson, David C.; Andorin, Antoine; Hochstadt, Aviram; Gourraud, Jean-Baptiste; Maeda, Shingo; Takahashi, Yoshihide; JM Juang, Jimmy; Kim, Sung-Hwan; Kamakura, Tsukasa; et al.
Abstract : Background: Brugada syndrome (BrS) is associated with mutations in the cardiac sodium channel gene, SCN5A. However, genetic studies of patients with BrS with arrhythmic events have been limited. We sought to compare various clinical, ECG, and electrophysiological parameters according to SCN5A genotype in a large cohort of BrS probands with first arrhythmic event. Methods: Survey on Arrhythmic Events in Brugada Syndrome is a survey of 10 Western and 4 Asian countries, gathering 678 patients with BrS with first arrhythmic event. Only probands were included, and SCN5A genotype adjudicated. Patients without appropriate genetic data were excluded. Associations of genotype with clinical features were analyzed. Results: The study group comprised 392 probands: 92 (23.5%) SCN5A+ (44 pathogenic/likely pathogenic [P/LP] and 48 variants of unknown significance) and 300 (76.5%) SCN5A−. SCN5A missense variants and the patients hosting them were similar regardless of adjudication. A higher proportion of patients with P/LP were pediatric (<16 years) compared with SCN5A− (11.4% versus 3%, P =0.023). The proportion of females was higher among patients with P/LP compared with SCN5A − (18.2% versus 6.3%, P =0.013). P/LP probands were more likely to have a family history of sudden cardiac death compared with SCN5A − (41.9% versus 16.8%, P <0.001). A higher proportion of patients with P/LP were White compared with SCN5A− (87.5% versus 47%, P <0.001). Ethnicity (odds ratio, 5.41 [2.8–11.19], P <0.001) and family history of sudden cardiac death (odds ratio, 2.73 [1.28–5.82], P =0.009) were independent variables associated with P/LP genotype following logistic regression. Conclusions: The genetic basis of BrS has a complex relationship with gender, ethnicity, and age. Probands hosting a P/LP variant tended to experience their first arrhythmic event at a younger age and to have events triggered by fever compared with patients with SCN5A− . In addition, they were more likely to be White and to have family history of sudden cardiac death. Among females, a P/LP variant suggests an increased risk of being symptomatic. This association should be further studied on an ethnically specific basis in large prospectively collected international cohorts. Abstract : Supplemental Digital Content is available in the text.